Fragment-oriented synthesis: β-elaboration of cyclic amine fragments using enecarbamates as platform intermediates. Issue 62 (6th July 2020) - Trindade, Alexandre F.; Faulkner, Emily L.; Leach, Andrew G.; Nelson, Adam; Marsden, Stephen P.
Abstract : Selective β-sp 3 functionalisation of cyclic amines is achieved through enecarbamate formation and photoredox-catalysed derivatisation with functionalised alkyl halides. Abstract : A strategy for the β-sp 3 functionalisation of cyclic amines is described. Regioselective conversion of protected amines to enecarbamates is achieved through electrochemical oxidation; these intermediates can be derivatised by functionalised alkyl halides under photoredox catalysis. The potential of the methods is highlighted by direct growth of a DCP2B-binding fragment.